(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In addition to a previous research, trials were carried out in 1997 to verify the effects of releases of O. laevigatus on the pollination of cherimoya in Sicily. The anthocorid confirmed its efficacy. Releases of O. laevigatus to improve the fruit setting and fruit quality of cherimoya, could be useful in orchards where the species is present at a low percentage and the efficacy of other species is poor. Hand pollination was tested using a small pump during 1998. Fruits produced through hand pollinated flowers were significantly more abundant and wellproportioned in comparison with those obtained in the control. The used technique allows to save time and labour considerably in comparison with the common hand pollination technique of using a small brush.